2024
DOI: 10.1021/acs.jafc.3c03901
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotic Administration Ameliorates Colitis and Inflammation in Rats Possibly through Gut Microbiota Modulation

Cuijiao Feng,
Chuantao Peng,
Weiqin Zhang
et al.

Abstract: Postbiotics are preparations of inanimate microorganisms and/or their components that are beneficial to host health. Compared with probiotics, the postbiotic dose required for exerting obvious protective effects is unknown. Thus, we conducted a dose-dependent postbiotic intervention study in dextran sulfate sodium (DSS)-induced colitis rats. The trial included five rat groups, including: control without DSS/postbiotic treatment, group C; 7-day DSS treatment, group D; 14-day low, medium, and high probiotic dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Lactobacillus , known for its positive influence on colonic barrier function, prevents cytokine-induced apoptosis of intestinal epithelial cells and increases Muc2 mRNA levels in vitro . Several studies have reported that interventions with probiotics, prebiotics, and postbiotics can significantly increase the abundance of Lactobacillus in the gut microbiota of mice. A high proportion of Bacteroidetes is associated with colitis resistance and low-grade systemic inflammation . Previous research has demonstrated that Enterorhabdus, which exhibited a negative correlation with pro-inflammatory cytokine levels, contributed positively to intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus , known for its positive influence on colonic barrier function, prevents cytokine-induced apoptosis of intestinal epithelial cells and increases Muc2 mRNA levels in vitro . Several studies have reported that interventions with probiotics, prebiotics, and postbiotics can significantly increase the abundance of Lactobacillus in the gut microbiota of mice. A high proportion of Bacteroidetes is associated with colitis resistance and low-grade systemic inflammation . Previous research has demonstrated that Enterorhabdus, which exhibited a negative correlation with pro-inflammatory cytokine levels, contributed positively to intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Odoribacter, considered beneficial, exhibits a negative correlation with the severity of nonalcoholic fatty liver disease (NAFLD) and IBD Alistipes and Prevotellaceae _UCG-001, associated with polysaccharide-digesting enzymes and SCFA production, alleviate glucose and lipid metabolism disorders through the AMP-activated protein kinase (AMPK) signaling pathway. , It was reported that a postbiotic product, derived from cell preparations of three probiotic strains, significantly enhanced the abundance of Odoribacter splanchnicus, Alistipes shahii, and Prevotella copri in colitis mice Faecalibacterium, widely present in the human gut, holds promise for next-generation probiotics or biotherapeutics.…”
Section: Discussionmentioning
confidence: 99%